Decompressive craniectomy following traumatic brain injury: developing the evidence base. (3rd March 2016) - Kolias, Angelos G.; Adams, Hadie; Timofeev, Ivan; Czosnyka, Marek; Corteen, Elizabeth A.; Pickard, John D.; Turner, Carole; Gregson, Barbara A.; Kirkpatrick, Peter J.; Murray, Gordon D.; Menon, David K.; Hutchinson, Peter J.
Abstract: In the context of traumatic brain injury (TBI), decompressive craniectomy (DC) is used as part of tiered therapeutic protocols for patients with intracranial hypertension (secondary or protocol-driven DC). In addition, the bone flap can be left out when evacuating a mass lesion, usually an acute subdural haematoma (ASDH), in the acute phase (primary DC). Even though, the principle of "opening the skull" in order to control brain oedema and raised intracranial pressure has been practised since the beginning of the 20th century, the last 20 years have been marked by efforts to develop the evidence base with the conduct of randomised trials. This article discusses the merits and challenges of this approach and provides an overview of randomised trials of DC following TBI. An update on the RESCUEicp study, a randomised trial of DC versus advanced medical management (including barbiturates) for severe and refractory post-traumatic intracranial hypertension is provided. In addition, the rationale for the RESCUE-ASDH study, the first randomised trial of primary DC versus craniotomy for adult head-injured patients with an ASDH, is presented.